2008
DOI: 10.1254/jphs.fm0070115
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Clinical Aspects of Non-neuronal Acetylcholine: Expression of Non-neuronal Acetylcholine in Urothelium and Its Clinical Significance

Abstract: Abstract.Recently, several reports demonstrate that non-neuronal acetylcholine (ACh) release may contribute to various pathophysiological conditions. In this review, we presented our experiments designed to evaluate the non-neuronal cholinergic system in human bladder. After insertion of the microdialysis probe, human bladder strips were suspended in an organ bath filled with Krebs-Henseleit solution, and Ringer solution was perfused into the probe. ACh release was measured by microdialysis and HPLC. The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 35 publications
0
57
1
1
Order By: Relevance
“…It is known that bladder epithelial cells express both muscarinic and alpha-1 adrenergic receptors, that these cells produce acetylcholine and ATP, and that afferent nerve terminals in the bladder express muscarinic and purinergic receptors (2,20). Therefore, acetylcholine produced by bladder epithelial cells may activate epithelial cells in an autocrine fashion via their muscarinic receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that bladder epithelial cells express both muscarinic and alpha-1 adrenergic receptors, that these cells produce acetylcholine and ATP, and that afferent nerve terminals in the bladder express muscarinic and purinergic receptors (2,20). Therefore, acetylcholine produced by bladder epithelial cells may activate epithelial cells in an autocrine fashion via their muscarinic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…These antagonists improve both urinary voiding disorders and urinary collecting disorders, while coadministration of the alpha-1 adrenergic receptor antagonist and the anti-muscarinic agent is more effective for controlling overactive bladder (OAB) in BPH patients (3). Anti-muscarinic agents are known to inhibit bladder smooth muscle contraction, and may possibly also block the effects of muscarinic receptors on bladder epithelial cells (12,20). Bladder epithelial cells exhibit a number of properties similar to those of neurons (nociceptors/mechanoreceptors), and both types of cells share several signal transduction mechanisms to detect physiological stimuli.…”
mentioning
confidence: 99%
“…Yoshida et al 67,68 demonstrated that there is a basal ACh release in human detrusor muscle. This release was resistant to TTX, and considerably reduced when the urothelium was removed, suggesting that the released ACh was of nonneuronal origin and, at least partly, generated by the urothelium.…”
Section: Local Mediators Influencing Spontaneous Activitymentioning
confidence: 99%
“…The expression of a non-neuronal cholinergic system in urinary bladder is reviewed in this issue by Yoshida et al (49). Briefly, they observed strong ChAT-positive immunostaining in the urothelial and suburothelial regions of the human urinary bladder (50).…”
Section: -4 Urinary Bladdermentioning
confidence: 99%